End electrode composition, laminated ceramic electronic component and preparation method thereof
This patent relates to laminated ceramic electronic components, particularly focusing on laminated ceramic electronic components with improved connectivity and durability.
Patent Information
- Application Number
- CN202310754886.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
AI Technical Summary
Existing methods for preparing electronic ceramics require a complex two-stage sintering process with the use of glass materials as sintering aids, leading to issues like glass aggregation, interface damage, structural defects, and poor electroplating, which are costly and time-consuming.
An end electrode composition comprising ceramic material, metal material, resin, and organic solvent, without the need for glass materials, ensuring excellent density and bonding with the ceramic body through a co-firing process.
This approach simplifies the process, reduces costs, and achieves better bonding, continuity, and reliability of the laminated ceramic electronic component, ensuring excellent connectivity and durability.
Smart Images

Figure CN119208014A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an end electrode composition, and also relates to a laminated ceramic electronic component using the end electrode composition and a manufacturing method thereof. Background Art
[0002] Electronic Ceramics include passive components such as multi-layer ceramic capacitors (MLCC), inductors and resistors. Due to their small size, they are widely used in automobiles, televisions, computers, mobile communications and other fields.
[0003] Since the structure of electronic ceramics is complex and includes ceramic layers, internal electrodes and end electrodes, how to properly combine the ceramic layers, internal electrodes and end electrodes is an important issue in the preparation of electronic ceramics. The traditional method of preparing electronic ceramics is to provide an end electrode composition to the ceramic body after the ceramic body of the electronic ceramic is sintered, and to electrically connect the end electrode formed by the end electrode composition to the ceramic body through a sintering step; wherein, the traditional end electrode composition must add glass material as a sintering aid, and the liquid phase formed by the glass material promotes the end electrode to produce a liquid phase sintering reaction or form a low-temperature eutectic phase, so that the end electrode is densified, and the end electrode and the ceramic body (including the internal electrode) are bonded to form a complete circuit. In other words, the traditional method of preparing electronic ceramics requires a two-stage sintering step to connect the ceramic layer, the internal electrode and the end electrode, which has the disadvantages of complex process and time-consuming.
[0004] Taking Chinese patent announcement number CN101658929B as an example, the copper-nickel alloy powder of the end electrode of the improved multilayer ceramic capacitor includes copper-nickel alloy powder A and copper-nickel alloy powder B; wherein the copper-nickel alloy powder A adopts physical vapor deposition to prepare spherical copper-nickel alloy powder with a particle size of 0.1 micron to 0.8 micron; copper-nickel alloy powder B adopts the traditional method, that is, the copper-nickel alloy powder A is flattened into a sheet copper-nickel alloy powder under pressure by a sand mill, thereby increasing the contact area between the end electrode and the inner electrode layer and improving the bonding force, so as to improve the welding performance of the end electrode, so that the multilayer ceramic capacitor is not easy to crack, and the product quality is improved. However, the use of physical vapor deposition has the disadvantage of high cost.
[0005] Therefore, how to prepare electronic ceramics in a more cost-effective way is an important problem to be continuously overcome. Summary of the invention
[0006] To solve the above problems, the present invention provides an end electrode composition, comprising a ceramic material, a metal material, a resin and an organic solvent; wherein, based on the total weight of the end electrode composition, the content of the ceramic material is 4 weight percent to 12 weight percent, the content of the metal material is 63 weight percent to 71 weight percent, the content of the resin is 1.3 weight percent to 11.5 weight percent, and the content of the organic solvent is 13 weight percent to 25 weight percent.
[0007] The present invention adjusts the content of ceramic material and metal material in the end electrode composition, so that even without adding glass material as a sintering aid, the obtained multilayer ceramic electronic component can still have excellent density of the end electrode, thereby simplifying the process and reducing costs.
[0008] Furthermore, when glass materials are added as sintering aids to conventional end electrode compositions, glass aggregation or vaporization is likely to occur at the end electrodes, resulting in the following problems: (1) problems that hinder the connection between the end electrodes and the inner electrodes; (2) the interface structure between the end electrodes and the ceramic body is damaged; (3) structural defects such as bubbles (blister) appear at the end electrodes; and (4) problems such as poor electroplating when other conductive layers are subsequently stacked on the end electrodes. In contrast, the end electrode composition of the present invention does not require the addition of glass materials, so there is no problem of glass floating or bubbles appearing. Furthermore, the end electrode composition of the present invention has the following advantages: (1) there is no situation where the end electrodes shrink excessively and cause the ceramic body to crack; (2) the laminated ceramic electronic component has no situation where the end electrodes and the ceramic body separate at the interface; (3) the laminated ceramic electronic component has excellent connection between the inner electrode and the end electrode, excellent continuity of the three-layer outer electrode, excellent weldability of the three-layer outer electrode, high capacitance tensile value and low capacitance discreteness.
[0009] Preferably, based on the total weight of the end electrode composition, the content of the ceramic material is 4 weight percent to 12 weight percent, for example, 4 weight percent, 5 weight percent, 6 weight percent, 7 weight percent, 8 weight percent, 9 weight percent, 10 weight percent, 11 weight percent or 12 weight percent; the content of the metal material is 63.75 weight percent to 70 weight percent, for example, 63.75 weight percent, 64 weight percent, 66 weight percent, 68 weight percent or 70 weight percent; the content of the resin is 1.5 weight percent to 11 weight percent, for example, 1.5 weight percent, 3 weight percent, 5 weight percent, 7 weight percent, 10 weight percent or 11 weight percent; and the content of the organic solvent is 14 weight percent to 23.5 weight percent, for example, 14 weight percent, 15 weight percent, 18 weight percent, 20 weight percent, 22 weight percent or 23.5 weight percent.
[0010] More preferably, based on the total weight of the end electrode composition, the content of the ceramic material is 7 weight percent to 8 weight percent; the content of the metal material is 67 weight percent to 68 weight percent; the content of the resin is 6 weight percent to 8 weight percent; and the content of the organic solvent is 16 weight percent to 19 weight percent.
[0011] In one embodiment, the ceramic material includes any one of barium titanate-based oxides and calcium zirconate-based oxides or a combination thereof.
[0012] Preferably, the barium titanate oxide comprises BaTiO3, BaTi4O9, Ba2Ti9O 20 any one or a combination of .
[0013] Preferably, the calcium zirconate oxide comprises any one of (SrCa)(ZrTi)O3, CaZrO3 or a combination thereof.
[0014] In one embodiment, the metal material comprises a base metal material. Preferably, the base metal material comprises copper, nickel or a combination thereof.
[0015] In one embodiment, the base metal material comprises a copper-nickel alloy, and based on the total weight of the metal material, the copper content is greater than 0 weight percent to less than 100 weight percent, for example: 1 weight percent, 10 weight percent, 25 weight percent, 50 weight percent, 75 weight percent or 99 weight percent; and the nickel content is greater than 0 weight percent to less than 100 weight percent, for example: 1 weight percent, 10 weight percent, 25 weight percent, 50 weight percent, 75 weight percent or 99 weight percent.
[0016] In one embodiment, the metal material is in a granular form. Preferably, the D50 particle size of the metal material is 0.5 micrometers to 10 micrometers. More preferably, the D50 particle size of the metal material is 1 micrometer to 5 micrometers. The D50 particle size refers to the particle diameter corresponding to 50% of the particles in the cumulative diameter distribution of the particles.
[0017] In one embodiment, the metal material is in the form of a sheet. Preferably, the longest diameter of the metal material is 2 micrometers to 10 micrometers.
[0018] In one embodiment, the ceramic material is a powder, and the D50 particle size of the ceramic material is 50 nanometers to 1000 nanometers. Preferably, the D50 particle size of the ceramic material is 230 nanometers to 260 nanometers.
[0019] According to the present invention, the D50 particle size range and the longest diameter range of the metal material, and the D50 particle size range of the ceramic material help to improve the dispersion uniformity of the metal material and the ceramic material in the end electrode composition.
[0020] In one embodiment, the resin includes any one of acrylic resin and ethyl cellulose resin or a combination thereof.
[0021] Preferably, the acrylic resin comprises any one of polymethyl acrylate (PMA), polyethyl acrylate (PEA), polymethyl methacrylate (PMMA), polyethyl methacrylate (PEMA), or a combination thereof.
[0022] The above-mentioned polymethyl methacrylate is also called acrylic resin.
[0023] Preferably, the ethyl cellulose resin comprises ethyl cellulose.
[0024] In one embodiment, the end electrode composition further includes any one or a combination of a thixotropic agent, a dispersant, a defoaming agent and a leveling agent.
[0025] Preferably, the thixotropic agent comprises polyamide wax. The end electrode composition of the present invention can further adjust the viscosity of the end electrode composition by adding the thixotropic agent.
[0026] Preferably, the dispersant comprises polyether phosphate. The end electrode composition of the present invention can further adjust the viscosity of the end electrode composition by adding the dispersant.
[0027] Preferably, the degassing agent comprises an ethylene polymer. The end electrode composition of the present invention further comprises the degassing agent, so that the end electrode composition can be degassed by itself, thereby reducing the risk of bubbles being entrained in the end electrode composition during the process of forming the end electrode.
[0028] Preferably, the leveling agent comprises a siloxane auxiliary agent having an alkyl aromatic group. The end electrode composition of the present invention further comprises the leveling agent, which can improve the surface flatness of the ceramic thin layer.
[0029] In one embodiment, the organic solvent comprises any one or a combination of alcohols, ethers and esters.
[0030] Preferably, the alcohol comprises any one of terpineol, cyclohexanemethanol, benzyl alcohol, 2-ethyl-1-hexanol, 1-octanol or a combination thereof.
[0031] The above-mentioned "cyclohexylmethanol" is also called hydrogenated terpineol.
[0032] Preferably, the ethers include ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, and diethylene glycol monoethyl ether.
[0033] Preferably, the esters include terpinyl dihydroacetate, terpinyl acetate, ethylene glycol diacetate, and 2-(2-ethoxyethoxy)ethyl acetate.
[0034] The above-mentioned "diethylene glycol ethyl ether" is also called carbitol.
[0035] The present invention further provides a multilayer ceramic electronic component, comprising:
[0036] A ceramic body, comprising a ceramic upper cover layer and a ceramic electrode staggered laminate, wherein the ceramic upper cover layer is disposed on the top of the ceramic electrode staggered laminate, wherein the ceramic electrode staggered laminate comprises multiple layers of ceramic electrode layers overlapping each other, and each of the multiple layers of ceramic electrode layers comprises a ceramic middle layer and an inner electrode, and the inner electrode is disposed on the top surface of the ceramic middle layer; and
[0037] Two end electrodes are respectively arranged on two opposite side surfaces of the ceramic body, and the two end electrodes are electrically connected to the inner electrodes of the multilayer ceramic electrode layer; wherein the two end electrodes each contain a metal material, a ceramic material and a sintering aid, and based on the total weight of any one of the two end electrodes, the content of the metal material is 83.5 weight percent to 93 weight percent, the content of the ceramic material is 6.5 weight percent to 16 weight percent, and the content of the sintering aid is greater than 0 weight percent to less than 3 weight percent.
[0038] First, although the end electrode composition of the present invention does not contain a sintering aid, the sintering aid contained in the ceramic body can flow to the end electrode through capillary phenomenon to promote the end electrode to undergo liquid phase sintering or low temperature eutectic phase reaction, so as to densify the end electrode and improve the bonding between the end electrode and the ceramic body. Second, the multilayer ceramic electronic component of the present invention has good bonding between the inner electrode and the end electrode, and has the advantage of high conductivity, which can reduce the heat generated by the multilayer ceramic electronic component due to power transmission loss, thereby reducing the risk of further affecting the reliability of the multilayer ceramic electronic component. Third, the end electrode of the present invention has a stable interface bonding force with the ceramic body, which can reduce the risk of the multilayer ceramic electronic component falling off due to vibration and thermal stress during use, thereby causing the multilayer ceramic electronic component to fail. Fourth, the end electrode of the present invention has excellent compactness, which can reduce the risk of poor contact or circuit short circuit caused by tin spraying or insufficient reflow at the end electrode or external electrode of the multilayer ceramic electronic component during the welding process of the circuit board assembly.
[0039] Preferably, based on the total weight of any one of the two end electrodes, the content of the metal material is 85 weight percent to 90 weight percent, for example, 85 weight percent, 87 weight percent, 89 weight percent or 90 weight percent; the content of the ceramic material is 7 weight percent to 15 weight percent, for example, 7 weight percent, 9 weight percent, 10 weight percent, 12 weight percent, 14 weight percent or 15 weight percent; and the content of the sintering aid is greater than 0 weight percent to less than 2 weight percent, for example, greater than 0 weight percent to less than 0.05 weight percent, greater than 0 weight percent to less than 0.1 weight percent, greater than 0 weight percent to less than 0.5 weight percent, greater than 0 weight percent to less than 1 weight percent, or greater than 0 weight percent to less than 2 weight percent.
[0040] Preferably, in the total weight of any of the two end electrodes, only the total weight of a single end electrode is calculated, and the single end electrode refers to an electrode directly connected to the inner electrode, and does not include an external electrode layer that is not directly connected to the inner electrode.
[0041] In one embodiment, the end electrode of the multilayer ceramic electronic component is further provided with at least one electrode layer to form an external electrode. Preferably, the external electrode is a three-layer external electrode, and the three-layer external electrode includes the end electrode, a nickel layer and a tin layer in sequence from the inside to the outside.
[0042] In one embodiment, the ceramic body includes a plurality of grains, and the length of the plurality of grains is 0.01 inch to 0.12 inch; and the width of the plurality of grains is 0.005 inch to 0.1 inch. Preferably, the size of the plurality of grains is any one of 0.12 inch×0.1 inch, 0.12 inch×0.06 inch, 0.08 inch×0.05 inch, 0.04 inch×0.02 inch, 0.02 inch×0.01 inch, 0.01 inch×0.005 inch, or a combination thereof. More preferably, the size of the plurality of grains is 0.01 inch×0.005 inch.
[0043] In one embodiment, the inner electrode comprises a base metal. Preferably, the base metal material comprises copper, nickel or a combination thereof.
[0044] In one embodiment, the ceramic body further includes a ceramic lower cover layer, and the ceramic electrodes are staggered and stacked on the top of the ceramic lower cover layer.
[0045] The present invention further provides a method for preparing a laminated ceramic electronic component, comprising:
[0046] The ceramic body blank preparation step includes molding a ceramic slurry into a multi-layer ceramic thin layer blank, wherein the multi-layer ceramic thin layer blank includes a ceramic upper cover layer blank and a multi-layer ceramic middle layer blank, wherein the ceramic slurry includes a ceramic body composition, and the ceramic body composition includes a ceramic component and a sintering aid;
[0047] An inner electrode blank is respectively arranged on the top surface of each of the ceramic intermediate layer blanks to obtain a multi-layer ceramic electrode layer blank;
[0048] Stacking the multiple layers of ceramic electrode layer embryos to obtain a ceramic electrode staggered layer embryo;
[0049] The ceramic upper cover layer blank is arranged on the top of the ceramic electrode staggered layer blank to obtain the ceramic body blank;
[0050] The end electrode blank arrangement step includes: arranging the end electrode composition as the end electrode blank on two opposite sides of the ceramic body blank to obtain a blank; and
[0051] Co-firing step: heating the green body at 900° C. to 1400° C. to obtain the laminated ceramic electronic component.
[0052] The preparation method of the laminated ceramic electronic component of the present invention heats the green embryo, that is, the ceramic body embryo and the end electrode embryo at the same time through a co-firing step. This is different from the traditional method of heating the ceramic body embryo and the end electrode embryo in two stages. It has the advantages of simplifying the process and saving energy and reducing carbon emissions, and is therefore cost-effective.
[0053] In one embodiment, based on the total weight of the ceramic body composition, the content of the ceramic component is 90 weight percent to 99 weight percent, and the content of the sintering aid is 1 weight percent to 10 weight percent.
[0054] In one embodiment, the ceramic component includes any one of barium titanate-based oxides and calcium zirconate-based oxides or a combination thereof.
[0055] Preferably, the barium titanate-based oxide comprises any one of BaTiO3 and BaTi4O9 or a combination thereof.
[0056] Preferably, the calcium zirconate oxide comprises any one of (SrCa)(ZrTi)O3, CaZrO3 or a combination thereof.
[0057] In one embodiment, the ceramic component in the ceramic body composition is the same as or different from the ceramic material in the end electrode composition.
[0058] In one embodiment, the sintering aid comprises silicon dioxide. Preferably, the sintering aid further comprises any one or a combination of metal oxides and metalloid oxides.
[0059] In one embodiment, the metal oxide comprises any one or a combination of MoO3, BaO, Al2O3, CaO and MgO.
[0060] In one embodiment, the metal oxide comprises B2O3.
[0061] In one embodiment, the sintering aid includes any one of BaO-Al2O3-SiO2, CaO-Al2O3-SiO2, MgO-Al2O3-SiO2, BaO-MgO-Al2O3-SiO2, CaO-MgO-Al2O3-SiO2, BaO-CaO-MoO3-MgO-Al2O3-SiO2, CaO-MnO-B2O3-SiO2 and BaO-ZnO-B2O3-SiO2 and their combinations.
[0062] In one embodiment, the inner electrode blank comprises a base metal, preferably copper, nickel or a combination thereof.
[0063] In one embodiment, the inner electrode blank is disposed on the top surface of each ceramic intermediate layer blank in a continuous, discontinuous or floating pattern.
[0064] The difference between the continuous type and the discontinuous type is that the inner electrodes on the same plane are a single whole in the continuous type, while the inner electrodes in the discontinuous type are divided into a plurality of blocks, and the blocks are not in direct contact with each other.
[0065] The difference between the continuous type and the floating type is that: one of the two ends of the internal electrode of the continuous type extends to a side surface of a ceramic body, and the two adjacent internal electrodes of the upper and lower layers each extend to the opposite side surface of the ceramic body; while the two adjacent internal electrodes of the floating type internal electrode are respectively: (i) the internal electrode area of the first plane is divided into two blocks, each block extends to the opposite side surfaces of the ceramic body, and the blocks are not directly in contact with each other; (ii) the internal electrode of the second plane is a single entity, and the single entity does not extend to any side surface of the ceramic body. In addition, the side surface of the ceramic body refers to the place where the end electrode is subsequently set.
[0066] In one embodiment, the thickness of the multi-layer ceramic thin layer blank is between 2 micrometers and 10 micrometers.
[0067] In one embodiment, the multi-layer ceramic thin layer embryo further includes a ceramic lower cover layer embryo, and the ceramic electrode staggered layer embryo is disposed on the top of the ceramic lower cover layer embryo.
[0068] In one embodiment, the co-firing step includes a burning step and a sintering step; wherein the burning step includes heating the green body at 300°C to 400°C for 10 hours to 14 hours to obtain a green body; and the sintering step includes heating the green body at 900°C to 1400°C for 1 hour to 3 hours to obtain the laminated ceramic electronic component.
[0069] Preferably, the heating temperature of the burning-out step and / or the sintering step is a maintained temperature.
[0070] Preferably, the heating temperature of the burning step is 340°C to 360°C.
[0071] Preferably, the heating time of the burning step is 11 hours to 13 hours.
[0072] Preferably, the heating temperature of the sintering step is 940°C to 1360°C.
[0073] Preferably, the heating time of the sintering step is 1.5 hours to 2.5 hours.
[0074] In one embodiment, the sintering step is performed in a sintering atmosphere. Preferably, the sintering atmosphere comprises nitrogen, hydrogen and oxygen, and the content of the oxygen is 5 ppm to 100 ppm. More preferably, when the metal material in the end electrode composition comprises copper, the sintering step is performed in the sintering atmosphere.
[0075] In summary, the end electrode composition of the present invention does not have glass material added as a sintering aid, so it has the advantages of simplifying the process and reducing costs; the multilayer ceramic electronic component of the present invention has good bonding between the inner electrode and the end electrode, a stable interface bonding force between the end electrode and the ceramic body, and excellent compactness of the end electrode, so the multilayer ceramic electronic component of the present invention has excellent reliability. Finally, the preparation method of the multilayer ceramic electronic component of the present invention has the advantages of simplifying the process and cost-effectiveness through the co-firing step: heating the green embryo, and heating the ceramic body embryo and the end electrode embryo at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 It is a schematic cross-sectional structure diagram of the multilayer ceramic electronic component of the present invention.
[0077] Figure 2 FIG. 1 is a flow chart of a method for manufacturing a multilayer ceramic electronic component of the present invention.
[0078] Figure 3 This is a photo of the ceramic body cracking due to excessive shrinkage of the end electrode.
[0079] Figure 4 This is a photograph showing that the connection between the inner electrode and the end electrode is excellent and there is no interface separation between the end electrode and the ceramic body.
[0080] Figure 5 This is a photo showing interface separation between the end electrode and the ceramic body.
[0081] Figure 6 This is a photo of the three-layer outer electrode exposed after being immersed in tin liquid. DETAILED DESCRIPTION
[0082] Several embodiments and comparative examples are listed below to illustrate the implementation methods of the present invention. Those skilled in the art can easily understand the advantages and effects that can be achieved by the present invention through the contents of this specification, and make various modifications and changes without departing from the spirit of the present invention to implement or apply the contents of the present invention.
[0083] 1. Example 1-1: Capacitor
[0084] (I) Structure of multilayer ceramic electronic components
[0085] The multilayer ceramic electronic component is a capacitor, such as Figure 1As shown, it comprises: a ceramic body 1 and two end electrodes 2A, 2B. The ceramic body 1 comprises a ceramic upper cover layer 10 and a ceramic electrode staggered laminate 11, and the ceramic upper cover layer 10 is arranged on the top of the ceramic electrode staggered laminate 11, wherein the ceramic electrode staggered laminate 11 comprises multiple ceramic electrode layers 110A, 110B overlapping each other, and the multiple ceramic electrode layers 110A, 110B each comprise a ceramic intermediate layer 1100A, 1100B and an internal electrode 1101A, 1101B, and the internal electrode 1101A is arranged on the top surface of the ceramic intermediate layer 1100A, and the internal electrode 1101B is arranged on the top surface of the ceramic intermediate layer 1100B. The two end electrodes 2A, 2B are respectively disposed on two opposite side surfaces of the ceramic body 1 , and the two side surfaces are perpendicular to the top surface of the ceramic body 1 , and the two end electrodes 2A, 2B are electrically connected to the internal electrodes 1101A, 1101B of the multilayer ceramic electrode layers 110A, 110B.
[0086] (II) Preparation method of multilayer ceramic electronic components
[0087] 1. As Figure 2 As shown, the preparation method of the laminated ceramic electronic component of the present invention first performs step S1: a ceramic body blank preparation step: a ceramic slurry is molded into a multi-layer ceramic thin layer embryo, and the multi-layer ceramic thin layer embryo can be used as a ceramic upper cover layer embryo and a multi-layer ceramic intermediate layer embryo respectively; an inner electrode embryo is respectively arranged on the top surface of each ceramic intermediate layer embryo to obtain a multi-layer ceramic electrode layer embryo; the multi-layer ceramic electrode layer embryo is stacked to obtain a ceramic electrode staggered laminated embryo; the ceramic upper cover layer embryo is arranged on the top of the ceramic electrode staggered laminated embryo to obtain the ceramic body blank.
[0088] Specifically, a ceramic body component, a dispersant and an organic solvent are mixed, ground and dispersed, and then a binder and a plasticizer are added and stirred to form a ceramic slurry; wherein, based on the total weight of the ceramic body component, the ceramic body component uses 99 weight percent of BaTiO3 and 1 weight percent of a sintering aid (i.e., BaO-CaO-MoO3-MgO-Al2O3-SiO2), the dispersant uses an anionic surfactant, the organic solvent uses a mixture of toluene and alcohol, and the volume ratio of the toluene to the alcohol is 1:1, the binder uses polyvinyl butyral resin, and the plasticizer uses phthalates. In addition, the D50 particle size of the ceramic material is 250 nanometers. Finally, the amount of dispersant, organic solvent, binder and plasticizer added can be adjusted according to demand.
[0089] The ceramic slurry is coated and formed into a ceramic thin layer embryo with a thickness of more than 2 microns by a foil casting method; wherein, a portion of the ceramic thin layer embryo is retained as a ceramic upper cover layer embryo and a ceramic lower cover layer embryo, and the remaining ceramic thin layer embryo is used as a ceramic intermediate layer embryo, and an internal electrode (i.e., a nickel metal electrode) embryo is printed on the top surface of each of the ceramic intermediate layer embryos by screen printing, and the pattern of the internal electrode embryo is continuous, so as to obtain a multi-layer ceramic electrode layer embryo, and after stacking the multi-layer ceramic electrode layer embryo, a ceramic electrode staggered layer embryo is obtained. Finally, after the ceramic electrode staggered layer embryo is set on the top surface of the ceramic lower cover layer embryo, the ceramic upper cover layer embryo is set on the top surface of the ceramic electrode staggered layer embryo to obtain the ceramic body embryo, and further after the layers of the ceramic body embryo are tightly combined by water equalization pressure, the size and appearance of the ceramic body embryo are modified by cutting and tumbling.
[0090] 2. Perform step S2: end electrode blank setting step: respectively set end electrode compositions on two opposite side surfaces of the ceramic body blank as the end electrode blank to obtain a blank.
[0091] Specifically, 7.5 weight percent of ceramic material (i.e., BaTi4O9), 67.5 weight percent of metal material (i.e., nickel), 7 weight percent of resin (i.e., polymethyl methacrylate), and 18 weight percent of organic solvent (i.e., pine alcohol) are stirred and dispersed uniformly in three rollers to obtain an end electrode paste, and the end electrode paste is disposed on two opposite side surfaces of the ceramic body blank by dipping to obtain a raw embryo; wherein the D50 particle size of the metal material is 3 microns.
[0092] 3. Perform step S3: co-firing step: heat the green body to obtain the laminated ceramic electronic component.
[0093] Specifically, a burning step is first performed: heating at 350°C for 12 hours to burn out the organic matter contained in the green embryo to obtain an embryo body, and then a sintering step is performed: heating at 1350°C for 2 hours to sinter the embryo body to obtain the laminated ceramic electronic component. Finally, a nickel layer and a tin layer are further added in sequence at the end electrode of the laminated ceramic electronic component by electroplating to obtain a finished product, that is, a capacitor with three layers of external electrodes, and the three layers of external electrodes sequentially include the end electrode, the nickel layer and the tin layer from the inside to the outside. In addition, the ceramic body of the laminated ceramic electronic component includes a plurality of grains, and the size specification of the plurality of grains is approximately 0.01 inches × 0.005 inches.
[0094] 2. Results Analysis
[0095] The following is an explanation of the results of Example 1-1 in order: the compactness of the end electrode, whether there is glass floating and bubbles appearing on the end electrode, whether the end electrode shrinks excessively and causes cracks in the ceramic body, the connection between the inner electrode and the end electrode, whether there is interface separation between the end electrode and the ceramic body, the continuity of the three-layer outer electrode, the weldability of the three-layer outer electrode, and the tensile force value of the capacitor and the coefficient of variation (COV) of the capacitance value.
[0096] (I) Density of end electrodes
[0097] Before the multilayer ceramic electronic component is further electroplated with a nickel layer and a tin layer to obtain a finished product, the compactness of the end electrode is first observed, and the steps include: 1. Grinding and polishing steps: using sandpaper (brand: 3M, specification: #1200) to grind the side of the multilayer ceramic electronic component where the end electrode is not set to obtain a grinded test product; wherein the volume of the grinded test product is only about one-half of the volume of the multilayer ceramic electronic component; using flannel cloth with 0.5 micron aluminum oxide powder to polish, to obtain a polished test product; wherein the polished test product has a polished surface. light side; 2. Fluorescence penetration method: the polished test product is immersed in a fluorescent liquid and then taken out and placed in a negative pressure environment (vacuumed) for 30 minutes to allow the fluorescent liquid to penetrate into the end electrode to obtain a test product that absorbs the fluorescent liquid; after the test product that absorbs the fluorescent liquid is dried, the laminated ceramic electronic component is ground with sandpaper (brand: 3M, specification: #1200) and polished with flannel cloth and 0.5 micron alumina powder to obtain a fluorescent test product; and 3. Analysis steps: A microscope that can observe fluorescence and Image pro-10 software are used to analyze the fluorescent penetration area on the side of the fluorescent test product to obtain the fluorescent penetration rate, which is divided into three levels: O means excellent, that is, the fluorescent penetration rate is less than 5%; △ means passing, that is, the fluorescent penetration rate is greater than or equal to 5% to 10%; X means failing, that is, the fluorescent penetration rate is greater than 10%, and the results are shown in Table 1-1.
[0098] (ii) Is there any glass floating out of the end electrode?
[0099] Before the laminated ceramic electronic component is further electroplated with nickel and tin layers to obtain the finished product, a scanning electron microscope is used to observe whether there is any glass floating on the outer surface of the end electrode. N indicates that the glass floating thickness is less than or equal to 10 microns, which is a pass; Y indicates that the glass floating thickness is greater than 10 microns, which is a fail. The results are shown in Table 1-1.
[0100] (III) Whether there are bubbles at the end electrode
[0101] Before the multilayer ceramic electronic component is electroplated with nickel and tin layers to obtain the finished product, the outer surface or the inside of the end electrode is observed to see if there are bubbles. The steps include: 1. The grinding and polishing steps described in (i) "Compactness of the end electrode" in "II. Result Analysis"; and 2. Analysis step: observe the outer surface of the ground test piece and the polished side with a microscope, and N represents no bubbles, which is a pass; Y represents bubbles, which is a fail. The results are shown in Table 1-1.
[0102] (IV) Whether the end electrode shrinks excessively and causes the ceramic body to crack
[0103] Before the multilayer ceramic electronic component is electroplated with nickel and tin layers to obtain the finished product, the end electrodes are first observed to see if they have shrunk excessively and caused cracks in the ceramic body. The steps include: 1. The grinding and polishing steps described in (i) "Density of the end electrodes" in "II. Result Analysis"; and 2. Analysis steps: Observe the outer surface of the ground test piece and the polished side surface under a microscope, and use N to indicate that the end electrode has not shrunk excessively, which is a pass; Y indicates that the end electrode has shrunk excessively, which is a fail. The results are shown in Table 1-1. In addition, the photo of the ceramic body cracking due to excessive shrinkage of the end electrode is shown in the figure below. Figure 3 As shown; wherein, the crack is as indicated by the arrow.
[0104] (V) Connection between inner electrode and end electrode
[0105] Before the laminated ceramic electronic component is further electroplated with nickel and tin layers to obtain the finished product, the connection between the inner electrode and the end electrode is first observed, and the steps include: 1. The grinding and polishing steps described in (i) "Compactness of the end electrode" in "II. Result Analysis"; and 2. Analysis step: Observe the polished side of the ground test piece under a microscope and divide it into three levels: O means excellent, that is, the connection rate between the inner electrode and the end electrode is greater than or equal to 70% to 100%; △ means passing, that is, the connection rate between the inner electrode and the end electrode is greater than or equal to 35% to less than 70%; X means failing, that is, the connection rate between the inner electrode and the end electrode is 0% to less than 35%. The results are shown in Table 1-2. In addition, the photo of the excellent connection between the inner electrode and the end electrode is shown in the figure below. Figure 4 shown.
[0106] (VI) Is there any interface separation between the end electrode and the ceramic body?
[0107] Before the laminated ceramic electronic component is further electroplated with nickel and tin layers to obtain the finished product, the end electrode is first observed to see if there is any interface separation from the ceramic body. The steps include: 1. The grinding and polishing steps described in (i) "Density of the end electrode" in "II. Result Analysis"; and 2. Analysis step: observe the polished side of the ground test piece under a microscope, and use N to indicate no interface separation, which is a pass; Y to indicate interface separation, which is a fail. The results are shown in Table 1-2. In addition, the photo of the end electrode and the ceramic body without interface separation is shown in Table 1-2. Figure 4 As shown in the figure, and the photo of the interface separation between the end electrode and the ceramic body is shown in the figure Figure 5 shown.
[0108] (VII) Continuity of the three-layer external electrode
[0109] After the laminated ceramic electronic component is further electroplated with a nickel layer and a tin layer to obtain a finished product, the continuity of the three-layer external electrode is observed, and the steps include: 1. Grinding and polishing steps: using sandpaper (brand: 3M, specification: #1200) to grind the side of the finished product where the three-layer external electrode is not set to obtain a ground finished product; wherein the volume of the ground finished product is only about one-half of the finished product; using flannel cloth with 0.5 micron aluminum oxide powder for polishing to obtain a polished finished product; wherein the polished finished product has a polished side; 2. Analysis step: observing the nickel layer in the polished side of the polished finished product through a microscope, and distinguishing it into three levels: O means excellent, that is, the nickel layer is continuous or uninterrupted; △ means passing, that is, the nickel layer has a break, and the length of the break is less than or equal to 25 microns; X means failing, that is, the nickel layer has a break, and the length of the break is greater than 25 microns, and the results are shown in Table 1-2.
[0110] (VIII) Weldability of three-layer external electrodes
[0111] After the multilayer ceramic electronic component is further electroplated with nickel and tin layers to obtain the finished product, the solderability of the three-layer external electrode is measured. The steps include: immersing the finished product in a 260°C tin solution for 30 seconds, and then observing the exposure ratio of the end electrode under a microscope, and dividing it into three levels: O means excellent, that is, the exposure ratio of the end electrode is less than or equal to 5%; △ means passing, that is, the exposure ratio of the end electrode is greater than 5% to 10%; X means failing, that is, the exposure ratio of the end electrode is greater than 10%. The results are shown in Table 1-2. In addition, the exposure of the end electrode is as shown in Table 1-2. Figure 6 As shown; wherein the circled portion is the exposed portion of the end electrode.
[0112] (IX) Capacitor tension value
[0113] After the multilayer ceramic electronic component is further electroplated with a nickel layer and a tin layer to obtain a finished product, the outer surfaces of the three layers of external electrodes on both sides of the capacitor are respectively soldered with iron wires using lead-free solder paste, and after the iron wires are clamped by a universal stretching machine, the tensile strength of the finished product is measured by pulling them up and down. The results are shown in Table 1-2; among them, the finished product is qualified when the tensile strength value is greater than 1.5 kgf, and the capacitor is unqualified when the tensile strength value is less than or equal to 1.5 kgf.
[0114] (10) Discreteness of capacitance value
[0115] After the multilayer ceramic electronic component is further electroplated with a nickel layer and a tin layer to obtain a finished product, the capacitance values of 30 finished products are measured using a capacitance meter (model: HP4278A) with a 1MHz AC signal and an external bias of 1Vrms, and the discreteness of the capacitance value is further calculated. The formula is: discreteness of capacitance value = (standard deviation of capacitance value / average value of capacitance value) × 100%; wherein, when the discreteness of capacitance value is less than or equal to 3%, it indicates that the yield of the capacitor will be excellent; when the discreteness of capacitance value is greater than 3% to less than or equal to 5%, it indicates that the yield of the capacitor will be acceptable; and when the discreteness of capacitance value is greater than 5%, it indicates that the yield of the capacitor will be unacceptable. The results are shown in Table 1-2.
[0116] Table 1-1: Compactness of the end electrode (referred to as "compactness"), glass floating (referred to as "glass floating") and bubble appearance (referred to as "bubbles") of Example 1-1, and the situation that the end electrode over-shrinks and causes the ceramic body to crack (referred to as "over-shrinkage")
[0117] Density Glass Floating bubble Over-contraction Example 1-1 O N N N
[0118] It can be seen from Table 1-1 that even though Example 1-1 does not add glass as a sintering aid to improve the density of the end electrode after sintering, the end electrode of Example 1-1 still has excellent density and does not have structural defects such as glass floating, bubbles or excessive shrinkage of the end electrode.
[0119] Table 1-2: Connection between the inner electrode and the end electrode of Example 1-1 (referred to as "connection condition"), separation between the end electrode and the ceramic body interface (referred to as "interface separation"), continuity of the three-layer outer electrode (referred to as "continuity"), weldability of the three-layer outer electrode (referred to as "weldability"), tensile value of the capacitor (referred to as "tensile value") and discrete rate of the capacitance value (referred to as "discrete rate")
[0120] Connection Interface separation Continuity Weldability Tensile force (kgf) Discreteness rate (%) Example 1-1 O N O O 2.16 1.3
[0121] As can be seen from Table 1-2, the connection between the inner electrode and the end electrode of Example 1-1 is excellent, and there is no separation between the end electrode and the ceramic body interface. In addition, the continuity and weldability of the three-layer outer electrode of Example 1-1 are both excellent. Finally, the tensile force value of the capacitor of Example 1-1 is as high as 2.16 kgf. It can be seen that the capacitor obtained by the co-firing method of the present invention has a tight connection between the end electrode and the ceramic body and has a low discrete rate of capacitance value.
[0122] III. Comparative Examples 1-1 to 1-21 and Examples 1-1 to 1-14
[0123] The main purpose of this experiment is to understand the feasible range of addition of ceramic materials and metal materials in the end electrode composition, so it is divided into four groups: Comparative Examples 1-1 to 1-7, Comparative Examples 1-8 to 1-14, Examples 1-1 to 1-7, Examples 1-8 to 1-14, Comparative Examples 1-15 to 1-21, as described below:
[0124] 1. Comparative Examples 1-1 to 1-7: The difference from Example 1-1 is that no ceramic material is added to Comparative Examples 1-1 to 1-7, and 75 weight percent of metal material is added;
[0125] 2. Comparative Examples 1-8 to 1-14: The difference from Example 1-1 is that Comparative Examples 1-8 to 1-14 all add 3.75 weight percent of ceramic material and 71.25 weight percent of metal material;
[0126] 3. Examples 1-1 to 1-7: Same as Example 1-1, except that 7.5 weight percent of ceramic material and 67.5 weight percent of metal material were added;
[0127] 4. Examples 1-8 to 1-14: The difference from Example 1-1 is that Examples 1-8 to 1-14 all add 11.25 weight percent of ceramic material and 63.75 weight percent of metal material;
[0128] 5. Comparative Examples 1-15 to 1-21: The difference from Example 1-1 is that Comparative Examples 1-15 to 1-21 all add 15 weight percent of ceramic material and 60 weight percent of metal material.
[0129] In addition, in the same group, the metal material in the end electrode composition, the metal composition of the inner electrode, the ceramic body composition and the sintering temperature were further adjusted to observe whether these parameters would have an impact on the capacitance.
[0130] Therefore, the preparation methods of Comparative Examples 1-1 to Comparative Examples 1-14, Examples 1-2 to Example 1-14, and Comparative Examples 1-15 to Comparative Examples 1-21 are similar to Example 1-1, wherein the only differences are the ceramic material content in the end electrode composition, the metal material and its content in the end electrode composition, the metal material in the end electrode composition, the metal component of the inner electrode, the ceramic body composition, and the sintering temperature, as shown in Table 2-1, and the contents shown in Table 2-1 are further explained as follows. Finally, the results of each group are analyzed as shown in Tables 2-2 and 2-3.
[0131] 1. In the section of “Metallic materials in the end electrode composition (hereinafter referred to as “metallic materials”)”: based on the total weight of the metal materials in the end electrode composition, the weight percentages of different metal materials are shown as the values in brackets.
[0132] 2. In the section “Metal composition of the inner electrode (referred to as “metal composition”)”:
[0133] Based on the total weight of the metal components of the inner electrode, the weight percentages of the different metal components are shown in the values in brackets.
[0134] 3. In the "Ceramic Body Composition" section:
[0135] (1) “I” indicates that the ceramic body composition includes 99 weight percent of ceramic component (i.e., BaTiO3) and 1 weight percent of sintering aid (i.e., BaO-CaO-MoO3-MgO-Al2O3-SiO2).
[0136] (2) “II” means that the ceramic body composition includes 99 weight percent of ceramic components (i.e., (SrCa)(ZrTi)O3) and 1 weight percent of sintering aid (i.e., CaO-MnO-B2O3-SiO2).
[0137] (3) "III" indicates that the ceramic body composition includes 97 weight percent of ceramic component (i.e., BaTiO3) and 3 weight percent of sintering aid (i.e., BaO-CaO-MoO3-MgO-Al2O3-SiO2).
[0138] (4) "IV" means that the ceramic body composition includes 90 weight percent of ceramic component (i.e., BaTi4O9) and 10 weight percent of sintering aid (i.e., BaO-ZnO-B2O3-SiO2).
[0139] (5) “V” indicates that the ceramic body composition includes 90 weight percent of ceramic component (i.e., CaZrO 3 ) and 10 weight percent of sintering aid (i.e., CaO—MnO—B 2 O 3 —SiO 2 ).
[0140] Table 2-1: Content of ceramic material (referred to as “ceramic material”) in the end electrode composition, content of metal material (referred to as “metal material”) in the end electrode composition, type of metal material, type of metal component of the inner electrode (referred to as “metal component”), composition of the ceramic body and sintering temperature of co-firing (referred to as sintering temperature) of Comparative Examples 1-1 to Comparative Examples 1-21 and Examples 1-1 to Examples 1-1 to Examples 1-14
[0141]
[0142]
[0143]
[0144] Table 2-2: Comparative Examples 1-1 to 1-14, Examples 1-1 to 1-14, and Comparative Examples 1-15 to 1-21: Comparative Examples 1-2 to 1-3, Comparative Examples 1-3 to 1-4, Comparative Examples 1-1 to 1-14, Comparative Examples 1-15 to 1-21: Comparative Examples 1-2 to 1-3, ...
[0145]
[0146]
[0147] It can be seen from Table 2-1 and Table 2-2 that even if the end electrode compositions of each group do not have any sintering aid added, especially Comparative Examples 1-1 to 1-7 do not have any ceramic material added, the end electrodes of each group still have excellent compactness, and there are no structural defects such as glass floating or bubbles. It can be seen that the sintering aid contained in the ceramic body embryo should be able to flow to the end electrode embryo through capillary phenomenon to promote the liquid phase sintering or low temperature eutectic phase reaction of the end electrode embryo to densify the end electrode. In addition, even if the sintering aid contained in the ceramic body embryo flows to the end electrode during the sintering process, there are no structural defects such as glass floating or bubbles in each group. It can be seen that the end electrode composition does not need to add a sintering aid. Finally, except for Comparative Examples 1-1 to 1-14, which all experienced excessive shrinkage of the end electrodes and caused cracks in the ceramic body, the end electrodes of the other groups did not have the structural defect of excessive shrinkage of the end electrodes. It can be seen that insufficient ceramic material (i.e., 0 weight percent or 3.75 weight percent) will cause the finished product to have the structural defect of excessive shrinkage of the end electrodes, while Examples 1-1 to 1-14 and Comparative Examples 1-15 to 21 that added a higher content of ceramic material did not have this problem.
[0148] Table 2-3: Connection between the inner electrode and the end electrode (referred to as "connection condition"), separation between the end electrode and the ceramic body interface (referred to as "interface separation"), continuity of the three-layer outer electrode (referred to as "continuity"), weldability of the three-layer outer electrode (referred to as "weldability"), tensile force value of the capacitor (referred to as "tensile force value"), and discrete rate of capacitance value (referred to as "discrete rate") of Comparative Examples 1-1 to Comparative Examples 1-21 and Examples 1-1 to Examples 1-14
[0149]
[0150]
[0151] As can be seen from Table 2-3, no ceramic material was added to any of Comparative Examples 1-1 to 1-7, resulting in the inability of the end electrode to adhere to the ceramic body, resulting in interface separation, and also making it impossible for the inner electrode and the end electrode to contact during the sintering process, resulting in a connection failure, and thus no need to measure the continuity of the three-layer outer electrode, the weldability of the three-layer outer electrode, and the tensile value of the capacitor. At the same time, based on the poor connection between the end electrode and the inner electrode or the ceramic body of Comparative Examples 1-1 to 1-7, the discrete rate of the capacitance value of Comparative Examples 1-1 to 1-7 also increased significantly, and all failed.
[0152] As for Comparative Examples 1-8 to 1-14, since Comparative Examples 1-8 to 1-14 all have ceramic materials (3.75 weight percent), the connection between the inner electrode and the end electrode, the continuity of the three-layer outer electrode, and the weldability of the three-layer outer electrode all have excellent analysis results. However, since Comparative Examples 1-8 to 1-14 have excessive shrinkage of the end electrode, resulting in cracks in the ceramic body, the tensile force of the capacitor is about 1.13 kgf to 1.16 kgf, which is only about half of that of Examples 1-1 to 1-14.
[0153] Regarding the parts of Comparative Examples 1-15 to 1-21, although Comparative Examples 1-15 to 1-21 also added ceramic materials (15 weight percent), Comparative Examples 1-15 to 1-21 all had poor connection between the inner electrode and the end electrode, resulting in a significant increase in the discrete rate of the capacitance value, and all failed. In addition, Comparative Examples 1-15 to 1-21 also had problems with poor continuity of the three-layer outer electrode and poor weldability of the three-layer outer electrode. It can be seen that when the amount of ceramic material added is too much (15 weight percent), although it can improve the adhesion between the end electrode and the ceramic body, and then improve the tensile force value (all greater than 2.6 kg force), too much ceramic material also causes it to be distributed between the end electrode and the inner electrode, resulting in the problem of poor connection between the end electrode and the inner electrode, and also reduces the adhesion between the end electrode and the three-layer outer electrode, thereby increasing the difficulty of subsequent preparation of the three-layer outer electrode.
[0154] Regarding the parts of Examples 1-1 to 1-14, Examples 1-1 to 1-7 all have ceramic materials added (7.5 weight percent), so the connection between the inner electrode and the end electrode is excellent, and there is no separation between the end electrode and the ceramic body interface. The amount of ceramic material added in Examples 1-8 to 1-14 is 11.25 weight percent. Although there is no separation between the end electrode and the ceramic body interface, the connection between the inner electrode and the end electrode is only acceptable. It can be seen that the amount of ceramic material added will indeed affect the connection between the inner electrode and the end electrode. Therefore, the ceramic material content in the end electrode composition can be 7.5 weight percent to 11.25 weight percent, and 7.5 weight percent is the best.
[0155] In addition, the continuity and weldability of the three-layer external electrodes of Examples 1-1 to 1-7 are both excellent, while the continuity and weldability of the three-layer external electrodes of Examples 1-8 to 1-14 are both acceptable. It can be seen that the ceramic material content in the end electrode composition can be 7.5 weight percent to 11.25 weight percent, and 7.5 weight percent is the best. Finally, the tensile strength values of the capacitors of Examples 1-1 to 1-14 are all excellent.
[0156] Regarding the sintering temperature of co-firing, examples 1-1 to 1-7 in Table 2-3 are taken as examples. Examples 1-1 to 1-7 increase the copper content contained in the metal material in sequence, and decrease the sintering temperature of the co-firing step in sequence, and all of them can obtain excellent finished products. It can be seen that increasing the copper content contained in the metal material can reduce the sintering temperature of co-firing, thereby further saving energy consumption.
[0157] In summary, based on the total weight of the end electrode composition, when the content of the ceramic material is 7.5 weight percent to 11.25 weight percent and the content of the metal material is 63.75 weight percent to 67.5 weight percent, the capacitor obtained by the co-firing method of the present invention has a tightly connected end electrode and a ceramic body, and the finished product has a low discrete rate of capacitance value. At the same time, according to embodiments 1 to 7 or embodiments 8 to 14, it can be seen that the end electrode composition of the present invention can adopt any type of base metal material and its alloy ratio; according to embodiments 1 to 7 or embodiments 8 to 14, it can be seen that the end electrode composition of the present invention can be matched with any base metal component of the inner electrode; according to embodiments 1 to 7 or embodiments 8 to 14, it can be seen that the end electrode composition of the present invention can be matched with a variety of ceramic body compositions, and the ceramic material in the end electrode composition does not need to be the same as the ceramic component in the ceramic body composition; and according to embodiments 1 to 7 or embodiments 8 to 14, it can be seen that the end electrode composition of the present invention can be matched with a variety of co-firing sintering temperatures.
[0158] IV. Comparative Examples 2-1 to 2-6, and Examples 2-1 to 2-6
[0159] The main purpose of this experiment is to understand the feasible range of ceramic and metal material additions when the ceramic material is replaced with (SrCa)(ZrTi)O3 in the end electrode composition, that is, the same ceramic composition as "ceramic body composition" II is used, as follows:
[0160] 1. Comparative Examples 2-1 to 2-3: The difference from Example 1-1 is that Comparative Examples 2-1 to 2-3 all add 3.75 weight percent of ceramic material and 71.25 weight percent of metal material;
[0161] 2. Examples 2-1 to 2-3: Same as Example 1-1, except that 7.5 weight percent of ceramic material and 67.5 weight percent of metal material were added;
[0162] 3. Examples 2-4 to 2-6: The difference from Example 1-1 is that Examples 2-4 to 2-6 all add 11.25 weight percent of ceramic material and 63.75 weight percent of metal material;
[0163] 4. Comparative Examples 2-4 to 2-6: The difference from Example 1-1 is that Comparative Examples 2-4 to 2-6 all add 15 weight percent of ceramic material and 60 weight percent of metal material.
[0164] In addition, the metal material in the end electrode composition, the metal composition of the inner electrode, the ceramic body composition and the sintering temperature are further adjusted to observe whether these parameters will affect the capacitance. Therefore, the preparation methods of Comparative Examples 2-1 to Comparative Examples 2-6 and Examples 2-1 to 2-6 are similar to those of Example 1-1, and the only difference is the ceramic material and its content in the end electrode composition, the metal material and its content in the end electrode composition, the metal material in the end electrode composition, the metal composition of the inner electrode, the ceramic body composition and the sintering temperature, as shown in Table 3-1. Finally, the results of each group are analyzed as shown in Table 3-2 and Table 3-3.
[0165] Table 3-1: Ceramic material content (hereinafter referred to as "ceramic material") in the end electrode composition of Comparative Examples 2-1 to Comparative Examples 2-6 and Examples 2-1 to Examples 2-6, metal material content (hereinafter referred to as "metal material") in the end electrode composition, type of metal material, type of metal component of the inner electrode (hereinafter referred to as "metal component"), ceramic body composition and sintering temperature of co-firing (hereinafter referred to as sintering temperature)
[0166]
[0167]
[0168] Table 3-2: Comparative Examples 2-1 to 2-6, ...
[0169] Density Glass Floating bubble Over-contraction Comparative Example 2-1 O N N Y Comparative Example 2-2 O N N Y Comparative Example 2-3 O N N Y Example 2-1 O N N N Example 2-2 O N N N Example 2-3 O N N N Embodiment 2-4 O N N N Embodiment 2-5 O N N N Embodiment 2-6 O N N N Comparative Examples 2-4 O N N N Comparative Examples 2-5 O N N N Comparative Examples 2-6 O N N N
[0170] As can be seen from Table 3-2, the analysis results of Comparative Examples 2-1 to 2-6 and Examples 2-1 to 2-6 are similar to those of Comparative Examples 1-8 to 1-21 and Examples 1-1 to 1-14, that is, the end electrodes of each group have excellent compactness and do not have structural defects such as glass floating or bubbles. In addition, Comparative Examples 2-1 to 2-3 add a small amount (3.75 weight percent) of ceramic material, so the end electrodes also have excessive shrinkage and cracks in the ceramic body, just like Comparative Examples 1-8 to 1-14, while the end electrodes of the other groups do not have structural defects such as excessive shrinkage of the end electrodes. Finally, from the various analysis results of Examples 2-1 to 2-6, it can be seen that the sintering aid contained in the ceramic body embryo can indeed densify the end electrode without adding a sintering aid to the end electrode composition.
[0171] Table 3-3: Connection between the inner electrode and the end electrode of Comparative Examples 2-1 to Comparative Examples 2-6 and Examples 2-1 to Examples 2-6 (referred to as "connection condition"), separation between the end electrode and the ceramic body interface (referred to as "interface separation"), continuity of the three-layer outer electrode (referred to as "continuity"), weldability of the three-layer outer electrode (referred to as "weldability"), tensile force value of the capacitor (referred to as "tensile force value") and discreteness rate of the capacitance value (referred to as "discreteness rate")
[0172] Connection Interface separation Continuity Weldability Tensile force (kgf) Discreteness rate (%) Comparative Example 2-1 O N O O 1.14 1.4 Comparative Example 2-2 O N O O 1.12 1.5 Comparative Example 2-3 O N O O 1.15 1.3 Example 2-1 O N O O 2.13 1.3 Example 2-2 O N O O 2.11 1.4 Example 2-3 O N O O 2.15 1.5 Embodiment 2-4 △ N △ △ 2.33 2.3 Embodiment 2-5 △ N △ △ 2.34 2.4 Embodiment 2-6 △ N △ △ 2.31 2.7 Comparative Examples 2-4 X N X X 2.69 6.5 Comparative Examples 2-5 X N X X 2.66 6.3 Comparative Examples 2-6 X N X X 2.65 6.7
[0173] It can be seen from Table 3-3 that the analysis results of Comparative Examples 2-1 to 2-6 and Examples 2-1 to 2-6 are similar to those of Comparative Examples 1-8 to 1-21 and Examples 1-1 to 1-14, that is, regarding the connection between the inner electrode and the end electrode, the continuity of the three-layer outer electrode and the weldability of the three-layer outer electrode, Comparative Examples 2-1 to 2-3 and Comparative Examples 1-8 to 1-14 all add 3.75 weight percent of ceramic material, and Examples 2-1 to 2-3 and Examples 1-1 to 1-7 all add 7.5 weight percent of ceramic material, so all have excellent analysis results, Examples 2-4 to 2-6 and Examples 1-8 to 1-14 all add 11.25 weight percent of ceramic material, so all have only passing analysis results, Comparative Examples 2-4 to 2-6 and Comparative Examples 1-15 to 1-21 all add 15 weight percent of ceramic material, so the analysis results are all unsatisfactory.
[0174] Regarding the tensile force value of the capacitor, Comparative Examples 2-1 to 2-3 and Comparative Examples 1-8 to 1-14 all added 3.75 weight percent of ceramic material. Since they also had the problem of excessive shrinkage of the end electrodes causing cracks in the ceramic body, the tensile force value of the capacitor was still significantly smaller, approximately only half of the tensile force value of Examples 2-1 to 2-6 and Comparative Examples 2-4 to 2-6.
[0175] In summary, even if different ceramic materials (i.e., (SrCa)(ZrTi)O3) are used, in the end electrode composition of the present invention, based on the total weight of the end electrode composition, it is still preferred that the content of the ceramic material is 7.5 weight percent to 11.25 weight percent, and the content of the metal material is 63.75 weight percent to 67.5 weight percent. In addition, according to the experimental results of Examples 2-2, 2-3, 2-5, and 2-6, the ceramic material in the end electrode composition does not need to be the same as the ceramic component in the ceramic body composition.
[0176] V. Comparative Examples 3-1 to 3-6, and Examples 3-1 to 3-6
[0177] The main purpose of this experiment is to understand the feasible range of ceramic and metal material additions when replacing the ceramic material with BaTiO3 in the end electrode composition, that is, using the same ceramic components as the "ceramic body composition" III, as explained below:
[0178] 1. Comparative Examples 3-1 to 3-3: The difference from Example 1-1 is that Comparative Examples 3-1 to 3-3 all add 3.75 weight percent of ceramic material and 71.25 weight percent of metal material;
[0179] 2. Examples 3-1 to 3-3: Same as Example 1-1, except that 7.5 weight percent of ceramic material and 67.5 weight percent of metal material were added;
[0180] 3. Examples 3-4 to 3-6: The difference from Example 1-1 is that Examples 3-4 to 3-6 all add 11.25 weight percent of ceramic material and 63.75 weight percent of metal material;
[0181] 4. Comparative Examples 3-4 to 3-6: The difference from Example 1-1 is that Comparative Examples 3-4 to 3-6 all add 15 weight percent of ceramic material and 60 weight percent of metal material.
[0182] In addition, the metal material in the end electrode composition, the metal composition of the inner electrode, the ceramic body composition and the sintering temperature are further adjusted to observe whether these parameters will affect the capacitance. Therefore, the preparation methods of Comparative Examples 3-1 to Comparative Examples 3-6 and Examples 3-1 to 3-6 are similar to those of Example 1-1, and the only difference is the ceramic material and its content in the end electrode composition, the metal material and its content in the end electrode composition, the metal material in the end electrode composition, the metal composition of the inner electrode, the ceramic body composition and the sintering temperature, as shown in Table 3-1. Finally, the results of each group are analyzed as shown in Table 3-2 and Table 3-3.
[0183] Table 4-1: Content of ceramic material (referred to as "ceramic material") in the end electrode composition of Comparative Examples 3-1 to Comparative Examples 3-6 and Examples 3-1 to Examples 3-6, content of metal material (referred to as "metal material") in the end electrode composition, type of metal material, type of metal component of the inner electrode (referred to as "metal component"), composition of the ceramic body and sintering temperature of co-firing (referred to as sintering temperature)
[0184]
[0185]
[0186] Table 4-2: Comparative Examples 3-1 to 3-6, ...1 to 3-6, Comparative Examples 3-6, Comparative Examples 3-6, Comparative Examples 3-6, Comparative Examples 3-1 to 3-6, Comparative Examples 3-6, Comparative Examples 3-6, Comparative Examples 3-1 to 3-6, Comparative Examples 3-
[0187] Density Glass Floating bubble Over-contraction Comparative Example 3-1 O N N Y Comparative Example 3-2 O N N Y Comparative Example 3-3 O N N Y Example 3-1 O N N N Example 3-2 O N N N Example 3-3 O N N N Embodiment 3-4 O N N N Embodiment 3-5 O N N N Embodiment 3-6 O N N N Comparative Examples 3-4 O N N N Comparative Examples 3-5 O N N N Comparative Examples 3-6 O N N N
[0188] As can be seen from Table 4-2, the analysis results of Comparative Examples 3-1 to 3-6 and Examples 3-1 to 3-6 are similar to those of Comparative Examples 2-1 to 2-6 and Examples 2-1 to 2-6, that is, the end electrodes of each group have excellent compactness and no structural defects such as glass floating or bubbles appear. In addition, only Comparative Examples 3-1 to 3-3 have excessive shrinkage of the end electrodes due to the addition of a small amount (3.75 weight percent) of ceramic material, which leads to cracking of the ceramic body, while the end electrodes of the other groups do not have structural defects such as excessive shrinkage of the end electrodes. Finally, from the various analysis results of Examples 3-1 to 3-6, it can be seen that the sintering aid contained in the ceramic body embryo can indeed densify the end electrode without adding a sintering aid to the end electrode composition.
[0189] Table 4-3: Connection between the inner electrode and the end electrode of Comparative Examples 3-1 to Comparative Examples 3-6 and Examples 3-1 to Examples 3-6 (referred to as "connection condition"), separation between the end electrode and the ceramic body interface (referred to as "interface separation"), continuity of the three-layer outer electrode (referred to as "continuity"), weldability of the three-layer outer electrode (referred to as "weldability"), tensile force value of the capacitor (referred to as "tensile force value") and discreteness rate of the capacitance value (referred to as "discreteness rate")
[0190] Connection Interface separation Continuity Weldability Tensile force (kgf) Discreteness rate (%) Comparative Example 3-1 O N O O 1.15 1.6 Comparative Example 3-2 O N O O 1.10 1.5 Comparative Example 3-3 O N O O 1.13 1.3 Example 3-1 O N O O 2.10 1.4 Example 3-2 O N O O 2.11 1.5 Example 3-3 O N O O 2.13 1.4 Embodiment 3-4 △ N △ △ 2.36 2.1 Embodiment 3-5 △ N △ △ 2.33 2.1 Embodiment 3-6 △ N △ △ 2.31 2.1 Comparative Examples 3-4 X N X X 2.66 6.3 Comparative Examples 3-5 X N X X 2.64 6.4 Comparative Examples 3-6 X N X X 2.61 6.6
[0191] As can be seen from Table 4-3, the analysis results of Comparative Examples 3-1 to 3-6 and Examples 3-1 to 3-6 are similar to those of Comparative Examples 2-1 to 2-6 and Examples 2-1 to 2-6. Therefore, even if a different ceramic material (i.e., BaTiO3) is used, in the end electrode composition of the present invention, based on the total weight of the end electrode composition, it is still preferred that the content of the ceramic material is 7.5 weight percent to 11.25 weight percent and the content of the metal material is 63.75 weight percent to 67.5 weight percent. In addition, according to the experimental results of Examples 3-1, 3-3, 3-4 and 3-6, the ceramic material in the end electrode composition does not need to be the same as the ceramic component in the ceramic body composition.
[0192] VI. Comparative Examples 4-1 to 4-6, and Examples 4-1 to 4-6
[0193] The main purpose of this experiment is to understand the effect of replacing ceramic material with Ba2Ti9O in the end electrode composition. 20 , that is, when using ceramic components that are different from the "ceramic body composition" I to V, the feasible range of addition amounts of ceramic materials and metal materials is as follows:
[0194] 1. Comparative Examples 4-1 to 4-3: The difference from Example 1-1 is that Comparative Examples 4-1 to 4-3 all add 3.75 weight percent of ceramic material and 71.25 weight percent of metal material;
[0195] 2. Examples 4-1 to 4-3: Same as Example 1-1, except that 7.5 weight percent of ceramic material and 67.5 weight percent of metal material were added;
[0196] 3. Examples 4-4 to 4-6: The difference from Example 1-1 is that Examples 4-4 to 4-6 all add 11.25 weight percent of ceramic material and 63.75 weight percent of metal material;
[0197] 4. Comparative Examples 4-4 to 4-6: The difference from Example 1-1 is that Comparative Examples 4-4 to 4-6 all add 15 weight percent of ceramic material and 60 weight percent of metal material.
[0198] In addition, the metal material in the end electrode composition, the metal composition of the inner electrode, the ceramic body composition and the sintering temperature are further adjusted to observe whether these parameters will affect the capacitance. Therefore, the preparation methods of Comparative Examples 4-1 to Comparative Examples 4-6 and Examples 4-1 to 4-6 are similar to those of Example 1-1, and the only difference is the ceramic material and its content in the end electrode composition, the metal material and its content in the end electrode composition, the metal material in the end electrode composition, the metal composition of the inner electrode, the ceramic body composition and the sintering temperature, as shown in Table 5-1. Finally, the results of each group are analyzed as shown in Table 5-2 and Table 5-3.
[0199] Table 5-1: Content of ceramic material (referred to as "ceramic material") in the end electrode composition of Comparative Examples 4-1 to Comparative Examples 4-6 and Examples 4-1 to Examples 4-6, content of metal material (referred to as "metal material") in the end electrode composition, type of metal material, type of metal component of the inner electrode (referred to as "metal component"), composition of the ceramic body and sintering temperature of co-firing (referred to as sintering temperature)
[0200]
[0201] Table 5-2: Comparative Examples 4-1 to 4-6, ...
[0202]
[0203] As can be seen from Table 5-2, the analysis results of Comparative Examples 4-1 to 4-6 and Examples 4-1 to 4-6 are the same as those of Comparative Examples 2-1 to 2-6, Examples 2-1 to 2-6, Comparative Examples 3-1 to 3-6, and Examples 3-1 to 3-6, that is, the end electrodes of each group have excellent compactness and no structural defects such as glass floating or bubbles appear. In addition, Comparative Examples 4-1 to 4-3 add a small amount (3.75 weight percent) of ceramic material, so the end electrodes also shrink excessively, resulting in cracks in the ceramic body, just like Comparative Examples 1-8 to 1-14, while the end electrodes of the other groups do not have structural defects such as excessive shrinkage of the end electrodes. It can be seen that the sintering aid contained in the ceramic body embryo can indeed make the end electrode compact, without adding a sintering aid to the end electrode composition.
[0204] Table 5-3: Connection between the inner electrode and the end electrode of Comparative Examples 4-1 to 4-6 and Examples 4-1 to 4-6 (referred to as "connection condition"), separation between the end electrode and the ceramic body interface (referred to as "interface separation"), continuity of the three-layer outer electrode (referred to as "continuity"), weldability of the three-layer outer electrode (referred to as "weldability"), tensile force value of the capacitor (referred to as "tensile force value") and discreteness rate of the capacitance value (referred to as "discreteness rate")
[0205] Connection Interface separation Continuity Weldability Tensile force (kgf) Discreteness rate (%) Comparative Example 4-1 O N O O 1.15 1.5 Comparative Example 4-2 O N O O 1.13 1.6 Comparative Example 4-3 O N O O 1.15 1.5 Example 4-1 O N O O 2.16 1.3 Example 4-2 O N O O 2.13 1.3 Example 4-3 O N O O 2.19 1.5 Example 4-4 △ N △ △ 2.34 2.1 Embodiment 4-5 △ N △ △ 2.33 2.1 Embodiment 4-6 △ N △ △ 2.36 2.4 Comparative Example 4-4 X N X X 2.65 6.8 Comparative Examples 4-5 X N X X 2.69 6.2 Comparative Examples 4-6 X N X X 2.60 6.3
[0206] As can be seen from Table 5-3, the analysis results of Comparative Examples 4-1 to 4-6 and Examples 4-1 to 4-6 are similar to those of Comparative Examples 2-1 to 2-6 and Examples 2-1 to 2-6 and Comparative Examples 3-1 to 3-6 and Examples 3-1 to 3-6. Therefore, even if a ceramic material different from the ceramic composition of "ceramic body composition" I to V (i.e., Ba2Ti9O 20 ), in the end electrode composition of the present invention, based on the total weight of the end electrode composition, the content of the ceramic material is still preferably 7.5 weight percent to 11.25 weight percent, and the content of the metal material is preferably 63.75 weight percent to 67.5 weight percent; at the same time, the ceramic material in the end electrode composition does not need to be the same as the ceramic component in the ceramic body composition.
[0207] VII. Example 5-1 to Example 5-8
[0208] The main purpose of this experiment is to understand the feasible resin type and content, the content range of the organic solvent, and the feasible method for preparing the ceramic electrode layer in the end electrode composition; wherein, the preparation methods of Examples 5-1 to 5-8 are similar to those of Examples 1-7 (that is, the ceramic material in the end electrode composition is 7.5 weight percent BaTi4O9, and the metal material is 67.5 weight percent copper), and the only difference from Examples 1-7 is: the resin type and content in the end electrode composition, the content of the organic solvent, the sintering temperature, and the method for preparing the ceramic electrode layer: screen printing, dipping, and rolling, to observe whether these parameters will affect the process, as described below and shown in Table 6-1:
[0209] 1. Examples 5-1 to 5-3: The difference from Example 1-1 is that the resins of Examples 5-1 to 5-3 all use ethyl cellulose, the resin content is 1.5 weight percent to 2.5 weight percent, and the organic solvent content is 22.5 weight percent to 23.5 weight percent;
[0210] 2. Examples 5-4 to 5-6: The difference from Example 1-1 is that the ceramic electrode layers of Examples 5-4 to 5-6 are prepared by dip coating, the resin content is 5 weight percent to 9 weight percent, and the organic solvent content is 16 weight percent to 20 weight percent;
[0211] 3. Examples 5-7 to 5-8: The difference from Example 1-1 is that the ceramic electrode layers of Examples 5-7 to 5-8 are prepared by roller coating, the resin content is 9 weight percent to 11 weight percent, and the organic solvent content is 14 weight percent to 16 weight percent.
[0212] In addition, since the adjustment of the content of the organic solvent will change the viscosity of the end electrode composition, Table 6-1 also provides the viscosity measured by a rotary viscometer at 10 rpm, and the unit is kilo counts per second (Kcps).
[0213] Table 6-1: Resin type, resin content, organic solvent content, viscosity of the end electrode composition (referred to as viscosity), and preparation method of the ceramic electrode layer (referred to as preparation method) in the end electrode composition of Examples 5-1 to 5-8
[0214]
[0215]
[0216] The appearance of the ceramic electrode layers obtained in Examples 5-1 to 5-8 is smooth, and there are no appearance defects such as pointed tips or sags. In addition, there is no problem of end electrode composition adhering to the screen in Examples 5-1 to 5-3. Therefore, the ceramic electrode layers obtained in Examples 5-1 to 5-8 are all conducive to the subsequent production of capacitors. In other words, the end electrode composition of the present invention can adopt different types of resins (ethyl cellulose or acrylic resin), and the resin content can be 1.5 weight percent to 11 weight percent, the organic solvent content can be 14 weight percent to 23.5 weight percent, and the method for preparing the ceramic electrode layer can adopt screen printing, dip coating or roller coating. It is particularly noted that the resin and organic solvent will be removed in the burning step, so the type and content of the resin and organic solvent do not affect the effect of the finished product.
[0217] In summary, in the preparation method of the laminated ceramic electronic component, through the co-firing step: heating the green embryo, the ceramic body embryo and the end electrode embryo can be sintered at the same time, which has the advantages of simplified process and cost-effectiveness. In addition, when the end electrode composition adopts ceramic materials and metal materials within a specific content range, even if no glass material is added as a sintering aid, the obtained laminated ceramic electronic component can still have excellent end electrode compactness, and the end electrode has no glass floating, no bubbles, and no end electrode excessive shrinkage causing the ceramic body to crack. At the same time, the laminated ceramic electronic component has no separation between the end electrode and the ceramic body interface, and has excellent connection between the inner electrode and the end electrode, continuity of the three-layer outer electrode, weldability of the three-layer outer electrode, high capacitance tensile force value and low capacitance value discrete rate. In other words, the obtained laminated ceramic electronic component has the advantages of high yield and high reliability.
Claims
1. An end electrode composition comprising a ceramic material, a metal material, a resin and an organic solvent; wherein: Based on the total weight of the end electrode composition, the content of the ceramic material is 4 weight percent to 12 weight percent, the content of the metal material is 63 weight percent to 71 weight percent, the content of the resin is 1.3 weight percent to 11.5 weight percent, and the content of the organic solvent is 13 weight percent to 25 weight percent.
2. The end electrode composition according to claim 1, wherein: The ceramic material comprises barium titanate series oxide, calcium zirconate series oxide or a combination thereof, and the metal material comprises a base metal material.
3. The end electrode composition according to claim 2, wherein: The barium titanate oxides include BaTiO3, BaTi4O9, Ba2Ti9O 20 Any one or a combination thereof; and the calcium zirconate oxide comprises any one or a combination of (SrCa)(ZrTi)O3, CaZrO3.
4. The end electrode composition according to claim 1, wherein: The resin comprises any one of acrylic resin and ethyl cellulose resin or a combination thereof; and the organic solvent comprises any one of alcohols, ethers and esters or a combination thereof.
5. The end electrode composition according to claim 1, wherein: The D50 particle size of the ceramic material is 50 nanometers to 1000 nanometers.
6. The end electrode composition according to claim 1, wherein: The metal material is in a granular form, and the D50 particle size of the metal material is 0.5 micrometers to 10 micrometers, or the metal material is in a flake form, and the longest diameter of the metal material is 2 micrometers to 10 micrometers.
7. A laminated ceramic electronic component comprising: A ceramic body, comprising a ceramic upper cover layer and a ceramic electrode staggered laminate, wherein the ceramic upper cover layer is disposed on the top of the ceramic electrode staggered laminate, wherein the ceramic electrode staggered laminate comprises multiple layers of ceramic electrode layers overlapping each other, and each of the multiple layers of ceramic electrode layers comprises a ceramic middle layer and an inner electrode, and the inner electrode is disposed on the top surface of the ceramic middle layer; and Two end electrodes are respectively arranged on two opposite side surfaces of the ceramic body, and the two end electrodes are electrically connected to the inner electrodes of the multilayer ceramic electrode layer; wherein the two end electrodes each contain a metal material, a ceramic material and a glass material, and based on the total weight of any one of the two end electrodes, the content of the metal material is 83.5 weight percent to 93 weight percent, the content of the ceramic material is 6.5 weight percent to 16 weight percent, and the content of the glass material is greater than 0 weight percent to less than 3 weight percent.
8. A method for preparing a laminated ceramic electronic component, comprising: The ceramic body blank preparation step is: a ceramic slurry is molded into a multi-layer ceramic thin layer blank, and the multi-layer ceramic thin layer blank includes a ceramic upper cover layer blank and a multi-layer ceramic middle layer blank, wherein: The ceramic slurry comprises a ceramic body composition, and the ceramic body composition comprises a ceramic component and a sintering aid; An inner electrode embryo is respectively arranged on the top surface of each of the ceramic intermediate layer embryos to obtain a multi-layer ceramic electrode layer embryo; Stacking the multi-layer ceramic electrode layer embryo to obtain a ceramic electrode staggered layer embryo; The ceramic upper cover layer embryo is arranged on the top of the ceramic electrode staggered layer embryo to obtain the ceramic body embryo; The end electrode blank arrangement step includes: arranging the end electrode composition as claimed in claim 1 on two opposite sides of the ceramic body blank as the end electrode blank to obtain a blank; as well as Co-firing step: heating the green body at 900° C. to 1400° C. to obtain the laminated ceramic electronic component.
9. The preparation method according to claim 8, wherein The ceramic component in the ceramic body composition includes any one of barium titanate-based oxides and calcium zirconate-based oxides or a combination thereof, and the ceramic component in the ceramic body composition is the same as or different from the ceramic material in the end electrode composition.
10. The preparation method according to claim 8, wherein The co-firing step includes a burning step and a sintering step; wherein the burning step includes heating the green embryo at 300° C. to 400° C. for 10 to 14 hours to obtain an embryo body; and the sintering step includes heating the embryo body at 900° C. to 1400° C. for 1 to 3 hours to obtain the laminated ceramic electronic component.
11. The preparation method according to claim 8, wherein The pattern form of the inner electrode embryos arranged on the top surface of each ceramic intermediate layer embryo is continuous, discontinuous or floating.